New South African species of the genus Idiasta Foerster, 1863 (Hymenoptera: Braconidae: Alysiinae), with a key to the Afrotropical and Malagasy taxa - Peris-Felipo, Francisco Javier; Belokobylskij, Sergey A. (Zootaxa, 2016)
A new species from South Africa, Idiasta iaiaorum sp. nov., is described and illustrated. A key for determination of the Afrotropical and Malagasy Idiasta species is provided.